Secrets of New Babylon - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale Kids, 2002)
Judd Thompson makes a startling discovery in New Babylon, and the Young Trib Force tries to avoid being trapped by the Global Community.
"The search for an imposter"--Cover.
5.5
5-8
Keywords: Christian fiction; Eschatology -- Fiction; Fantasy; Teenagers -- Fiction; Christian fiction; Eschatology -- Fiction; Teenagers -- Fiction; Fantastic fiction